El Modelo de Representación de los Trabajadores en la Empresa en el Sistema de Relaciones Laborales Español. Algunas Ideas Para el Debate - Nieto Rojas, Patricia (2016)
In the Spanish legal system, the workplace employee representation but may have certain similarities with the political representation (regulatory origin, not voluntary for the principal, democratic legitimacy) poses a specificity both the subjective perspective, to be circumscribed workers who make up the constituency, as a material arises as to represent the professional interests shared by a community of individuals united by an identical legal relationship derived from belonging to the same company. Its uniqueness is that this function can be assumed, concurrently, for two types: some representatives of elective basis; others, union base. This legal decision set a pluralistic model of subjects, but strongly interconnected functional dimension, due to differing legal natures.